Thrombin enhances NGF-mediated neurite extension via increased and sustained activation of p44/42 MAPK and p38 MAPK. - Rania E Mufti; Krishna Sarker; Yan Jin; Songbin Fu; Jesusa L Rosales; Ki-Young Lee (PLoS ONE, 2014)
Rapid neurite remodeling is fundamental to nervous system development and plasticity. It involves neurite extension that is regulated by NGF through PI3K/AKT, p44/42 MAPK and p38 MAPK. It also involves neurite retraction that is regulated by the serine protease, thrombin. However, the intracellular signaling pathway by which thrombin causes neurite retraction is unknown. Using the PC12 neuronal cell model, we demonstrate that thrombin utilizes the PI3K/AKT pathway for neurite retraction in NGF-differentiated cells. Interestingly, however, we found that thrombin enhances NGF-induced neurite extension in differentiating cells. This is achieved through increased and sustained activation of p44/42 MAPK and p38 MAPK. Thus, thrombin elicits opposing effects in differentiated and differentiating cells through activation of distinct signaling pathways: neurite retraction in differentiated cells via PI3K/AKT, and neurite extension in differentiating cells via p44/42 MAPK and p38 MAPK. These findings, which also point to a novel cooperative role between thrombin and NGF, have significant implications in the development of the nervous system and the disease processes that afflicts it as well as in the potential of combined thrombin and NGF therapy for impaired learning and memory, and spinal cord injury which all require neurite extension and remodeling.